Functional changes between seasons in the male songbird auditory forebrain - De Groof, Geert; Poirier, Colline; George, Isabelle; Hausberger, Martine; Van der Linden, Annemie (Frontiers in Behavioral Neuroscience, 2013)
Songbirds are an excellent model for investigating the perception of learned complex acoustic communication signals. Male European starlings (Sturnus vulgaris) sing throughout the year distinct types of song that bear either social or individual information. Although the relative importance of social and individual information changes seasonally, evidence of functional seasonal changes in neural response to these songs remains elusive. We thus decided to use in vivo functional magnetic resonance imaging (fMRI) to examine auditory responses of male starlings that were exposed to songs that convey different levels of information (species-specific and group identity or individual identity), both during (when mate recognition is particularly important) and outside the breeding season (when group recognition is particularly important). We report three main findings: (1) the auditory area caudomedial nidopallium (NCM), an auditory region that is analogous to the mammalian auditory cortex, is clearly involved in the processing/categorization of conspecific songs; (2) season-related change in differential song processing is limited to a caudal part of NCM; in the more rostral parts, songs bearing individual information induce higher BOLD responses than songs bearing species and group information, regardless of the season; (3) the differentiation between songs bearing species and group information and songs bearing individual information seems to be biased towards the right hemisphere. This study provides evidence that auditory processing of behaviourally-relevant (conspecific) communication signals changes seasonally, even when the spectro-temporal properties of these signals do not change.